KARAKTERISTIK PENGEMIS PEREMPUAN DI KECAMATAN TLANAKAN KABUPATEN PAMEKASAN - Supraptiningsih, Umi (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2016)
The constitution 1945 has guaranteed the poor and neglected children as stated in Article 34. The homeless, beggars and street children can also be categorized as poor that are maintained by the state. In fact, the portraits of beggars, especially in Pamekasan regency have become a spectacle and terrible habits. The question is whether the beggars obviously meet the criteria of the poor? This is what we need to look deeply as begging become habit or living. In this study, the researcher wanted to know and map the characteristics of female beggars in the District of Tlanakan Pamekasan. Beggarâs view and understanding of the needs of life is merely about to eat and to drink. The desire to stop their habits and having a job may become solutions for them to fill their needs. Female beggars actually have a psychological concern when they are begging in the streets, shopping centers, government offices, and door to door. They feel ashamed to even if peopleâs responds and attitude towards them are normal. They desired to end the habits as they are old and no longer be able to walk; so that, they do an easy thing to support their own needs.